Gestión comercial de la Microempresa Yahvé Jireh de la ciudad de Babahoyo periodo 2021. - Sánchez Figueroa, Jessica Pamela (2022)
The microenterprise Yavhe Jireh is located in the city of Babahoyo, dedicated to the economic activity of selling food products and basic necessities, where there is a decrease in its level of sales due to shortcomings in the commercial management of the establishment, this due to the absence of strategies and procedures that are developed following a planning to reach the audience effectively and get their commercial preference. In this way, the case was studied in depth taking as a basis direct and indirect sources of study, in order to have knowledge of the internal and external factors that affect the commercialization of the products of the business, with this it was possible to make an analysis of data and consequently deduce real arguments concerning the situation raised.